Advances in Microbial and Plant-Based Biopolymers: Synthesis and Applications in Next-Generation Materials - Poova Kattil Drishya; M. Venkateswar Reddy; Gunda Mohanakrishna; Omprakash Sarkar; Isha; M. V. Rohit; Aesha Patel; Young-Cheol Chang (Macromol, 2025)
Biopolymers are revolutionizing the materials landscape, driven by a growing demand for sustainable alternatives to traditional petroleum-based materials. Sourced from biological origins, these polymers are not only environment friendly but also present exciting solutions in healthcare, packaging, biosensors, high performance, and durable materials as alternatives to crude oil-based products. Recently, biopolymers derived from plants, such as lignin and cellulose, alongside those produced by bacteria, like polyhydroxyalkanoates (PHAs), have captured the spotlight, drawing significant interest for their industrial and eco-friendly applications. The growing interest in biopolymers stems from their potential as sustainable, renewable materials across diverse applications. This review provides an in-depth analysis of the current advancements in plant-based and bacterial biopolymers, covering aspects of bioproduction, downstream processing, and their integration into high-performance next-generation materials. Additionally, we delve into the technical challenges of cost-effectiveness, processing, and scalability, which are critical barriers to widespread adoption. By highlighting these issues, this review aims to equip researchers in the bio-based domain with a comprehensive understanding of how plant-based and bacterial biopolymers can serve as viable alternatives to petroleum-derived materials. Ultimately, we envision a transformative shift from a linear, fossil fuel-based economy to a circular, bio-based economy, fostering more sustainable and environmentally conscious material solutions using novel biopolymers aligning with the framework of the United Nations Sustainable Development Goals (SDGs), including clean water and sanitation (SDG 6), industry, innovation, and infrastructure (SDG 9), affordable and clean energy (SDG 7), sustainable cities and communities (SDG 11), responsible production and consumption (SDG 12), and climate action (SDG 13).